2004
DOI: 10.1111/j.1529-8817.2003.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and transient response of soil respiration to rain

Abstract: The influence of rainstorm on soil respiration of a mixed forest in southern New England, USA was investigated with eddy covariance, rain simulation and laboratory incubation. Soil respiration is shown to respond rapidly and instantaneously to the onset of rain and return to the prerain rate shortly after the rain stops. The pulse-like flux, most likely caused by the decomposition of active carbon compounds in the litter layer, can amount to a loss of 0.18 t C ha À1 to the atmosphere in a single intensive stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
186
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(212 citation statements)
references
References 38 publications
22
186
1
3
Order By: Relevance
“…The strong dependence of FLD on moisture conditions was evidenced by the marked difference between sites in July 2002 and September 2003. The link between leaf litter decomposition and moisture has been documented by Lee et al (2004) who found a linear decrease in the relative contribution of the litter layer with lower litter water contents in a manipulated study in a mixed forest. In a tropical forest, an indication of the dependence of FLD on litter moisture content was observed by Goulden et al (2004) when patterns of soil respiration rates varied in concert with the moisture content of the surface leaf litter.…”
Section: Leaf Litter Decompositionmentioning
confidence: 99%
“…The strong dependence of FLD on moisture conditions was evidenced by the marked difference between sites in July 2002 and September 2003. The link between leaf litter decomposition and moisture has been documented by Lee et al (2004) who found a linear decrease in the relative contribution of the litter layer with lower litter water contents in a manipulated study in a mixed forest. In a tropical forest, an indication of the dependence of FLD on litter moisture content was observed by Goulden et al (2004) when patterns of soil respiration rates varied in concert with the moisture content of the surface leaf litter.…”
Section: Leaf Litter Decompositionmentioning
confidence: 99%
“…The Mediterranean climate is characterized by summer droughts that particularly affect the top soil layers; therefore, rainfall events during these dry periods can trigger abrupt increases in SR that last for days (Bowling et al, 2011;Cisneros-Dozal et al, 2007;Lee et al, 2004;Unger et al, 2010). Lee et al (2004) simulated precipitation and found that hardwood forest floors were very sensitive to changes in moisture in the upper soil layers.…”
Section: Rain Pulse and Drought Effects On Srmentioning
confidence: 99%
“…In peat plateau, the lower layer (21 to 40 cm) contributed about only 5% of SR, which could be due to the presence of the water table. Peat plateau areas exhibited greater variability in the flux with a pronounced increase in the CO 2 emissions after rain events, which can be attributed to increased decomposition [26] or displacement of soil-stored CO 2 [30]. …”
Section: Time Series Of Nce and Ermentioning
confidence: 99%
“…In peat plateau, the lower layer (21 to 40 cm) contributed about only 5% of SR, which could be due to the presence of the water table. Peat plateau areas exhibited greater variability in the flux with a pronounced increase in the CO2 emissions after rain events, which can be attributed to increased decomposition [26] or displacement of soil-stored CO2 [30]. Calculated flux contributions from different soil layers using the CO 2 gradient technique showed that in both peat plateau (PP) and upland (UL) areas, the greatest contribution (about 75%) of soil respiration (SR) originated in the upper 5 cm layer (Figure 7).…”
Section: Time Series Of Nce and Ermentioning
confidence: 99%